(untitled) (GEON Journal (Management, Organizations and Business), 2021)
For a few decades now, work has been done in depth on scientific research on evidence in talent management companies. At a professional level, there have already been many organizations that have made the qualitative leap towards a new way of approaching human resources (HR). Mainly because this new perspective is more linked to both business and business objectives, as well as being more accepted by most professionals. From the origins of the Mckinsey War for Talent to the present, research is looking at the role of talent management in organizational results. In this sense, Luna (2018) designed a talent management model based on seven variables: the 7GT model. This model contains three systemic variables that control the entire organization and four strategic variables, and in addition to being implemented in many organizations, it is also being scientifically investigated. In the same way, Luna (2021) realized that it would be useless to formulate a new way of managing people based on talent if there was no change in the leadership of a large part of the organizations. For this reason, he designed a six-variable model to lead from talent. The implications of both models in the organizational and business world are analyzed, as well as the variables that compose it.